Post Partum Depression and Social Support. An Exploration of Experiences of New Mothers with Postpartum Depression in Tirana - MeÃ§e, Daniela (Mediterranean Journal of Social Sciences, 2012)
The main purpose of this study was to make an exploration of the experiences of new mothers with postpartumdepression symptoms. This study focuses on the perceptions of new mothers of the relationship they have with themselves, thenewborn, and their close family members. The study evaluates the importance of social support in development of postpartumdepression and facing stressful psychosocial factors. The study was conducted in Tirana and the target group was made of newmothers, six weeks to one year after birth. The Edinburgh Postpartum Depression Scale (EPDS) was used to asses post partumdepression. Significant Others Scale (SOS) was used to asses social support. In depth interviews are used to obtain informationon the experiences of women with PPD.Results of the study showed lack of information related to PPD. Interviews provided a lotof information related to the situation of new mothers with PPD and the factors that may have affected their condition. Such are:child health, financial problems, problems with the spouse, and lack of social support. Social support as one of the mainvariables in the study presented was an important factor in the development of PPD. The study showed a connection betweenlack of social support and PPD.This study revealed skepticism of new mothers with PPD symptoms to seek specialist help andto talk about their problems with people outside of the family.The study confirmed the fact that post partum depression iscurrently a problem for new mothers.